The Constant Annual Premium and Benefit Reserve for Four Participants in Joint Life Insurance - Nindita Nadilia; Nina Fitriyati; Irma Fauziah (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2020)
AbstractThis research discusses the derivation of formula to calculate the constant annual premiums and the benefit reserves for joint insurance consisting of four people. We combine pure endowment insurance, lifetime insurance, and n-year term insurance. Assumed that the benefits are set at the beginning of the insurance contract, the benefit reserves are calculated using the prospective method, and the premium payment stops if one of those four participants dies. If all participants live until the end of the contract, the benefits are paid at once but if one of the participants dies, the benefits paid at the end of the contract in the form of a lifetime annuity. The formula to calculate the benefit reserves is divided into four cases i.e. the benefit reserves if one of four participants dies, the benefit reserves if two of four participants die, the benefit reserve if three of four participants die, and the benefit reserves if all participants are still alive until the end of the contract. Besides, we also present simulation to calculate the constant annual premium for four participants consist of a father (50 years old), a mother (45 years old), a son (20 years old), and a daughter (15 years old). From the simulation, we conclude that as the length of the insurance contract increases, the premium tends to decrease. The benefit reserve calculation does not have a certain tendency. It generally increases during the insurance period (the premium is still paid) and then decreases thereafter. This is valid for all cases mentioned above.Keywords: n-year term insurance; prospective method; pure endowment insurance. AbstrakPenelitian ini membahas mengenai penurunan rumus untuk menghitung premi tahunan konstan dan cadangan benefit untuk asuransi gabungan yang terdiri dari empat orang. Jenis asuransi yang digunakan adalah kombinasi antara asuransi endowment murni, asuransi seumur hidup dan asuransi berjangka n-tahun. Diasumsikan bahwa benefit ditetapkan di awal kontrak asuransi dan pembayaran premi berhenti jika salah seorang dari keempat peserta meninggal dunia. Jika seluruh peserta hidup sampai dengan akhir kontrak maka benefit dibayarkan secara sekaligus, namun jika salah satu dari peserta telah meninggal dunia maka benefit yang dibayarkan pada akhir tahun kontrak dalam bentuk anuitas seumur hidup. Rumus yang diperoleh untuk menghitung cadangan benefit dibagi menjadi empat kasus yaitu cadangan benefit jika satu orang meninggal dan tiga orang lainnya hidup, cadangan benefit jika dua orang meninggal dan dua orang lainnya hidup, cadangan benefit jika tiga orang meninggal dan satu orang lainnya hidup, dan cadangan benefit jika semua peserta tetap hidup sampai akhir masa kontrak. Pada akhir penelitian, disajikan simulasi perhitungan premi tahunan konstan untuk empat peserta yang terdiri dari ayah (berusia 50 tahun), ibu (45 tahun), anak laki-laki (20 tahun), dan anak perempuan (15 tahun). Dari simulasi diperoleh bahwa semakin lama kontrak asuransi maka premi yang dibayakan cenderung semakin kecil. Perhitungan cadangan benefit tidak memiliki kecenderungan tertentu, namun pada umumnya meningkat selama masa asuransi berlangsung (pembayaran premi masih dilakukan) kemudian menurun setelahnya. Hal ini berlaku untuk seluruh kasus yang telah dibahas pada perhitungan rumus cadangan premi.Kata kunci: asuransi berjangka n-tahun; metode prospektif; asuransi endowment murni.